Do you want to get healthier with Facebook? - Adzharuddin, Nor Azura; Mohd Ramly, Norazmie; Ismail, Suriani (Centre for Promoting Ideas, 2014)
Recent development in information and communication technologies has given positive impacts in the field of health communication. Sharing of information which is related to health becomes easier with the advent of new technologies such as social media networks because it helps promote interactive communication. There are a variety of social media sites can be accessed by users, such as Facebook, Twitter, LinkedIn and Microblogs. Conventional health communication strategies that include putting up posters, distributing leaflets and delivering talks on health are inadequate in the fast moving era of modern society. In contrast to the conventional health communication, new technology is believed to be more interactive because it involves visual, audio and animation simultaneously, thus it is more accessible and interactive. This article discusses the usage of social media intervention namely Facebook and to realize its ability in assisting and providing health information that can create awareness among the public.